Circulating myeloid-derived suppressor cells and regulatory T cells as immunological biomarkers in refractory/relapsed diffuse large B-cell lymphoma: translational results from the R2-GDP-GOTEL trial. Issue 6 (22nd June 2021) - Jiménez-Cortegana, Carlos; Palazón-Carrión, Natalia; Martin Garcia-Sancho, Alejandro; Nogales-Fernandez, Esteban; Carnicero-González, Fernando; Ríos-Herranz, Eduardo; de la Cruz-Vicente, Fatima; Rodríguez-García, Guillermo; Fernández-Álvarez, Rubén; Rueda Dominguez, Antonio; Casanova-Espinosa, Maria; Martínez-Banaclocha, Natividad; et al.
Abstract : Background: The search for immunological markers with ability of predicting clinical outcome is a priority in lymphomas, and in cancer in general. It is well known that some immunomodulatory cells, such as myeloid derived suppressor cells (MDSCs) or regulatory T cells (Tregs), are recruited by tumors, jeopardizing antitumor immunosurveillance. In this work, we have studied blood levels of these immunosuppressive cells in patients with relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL), prior to and along the course of the experimental rituximab, gemcitabine, dexamethasone, and cisplatin (R2-GDP) schedule, as a translational substudy of the R2-GDP-GOTEL trial (EudraCT Number: 2014-001620-29), which included lenalidomide as an immunomodulator. Methods: Blood samples were taken before treatment, at cycle 3 and end of induction. Samples were analyzed by flow cytometry. Non-parametric tests were used. Mann-Whitney U test was used to compare basal cells distributions, and Wilcoxon test was considered to compare cells distribution at different times. Spearman test was performed to measure the degree of association between cell populations. Results: In this study, MDSC and Treg circulating concentration was found increased in all patients compared with a healthy control group and decreased after treatment only in patients with longest overall survival (>24 months), reaching the levels of the healthy group. Likewise, the number of inhibited T lymphocytes expressing Programmed Death-1 (PD-1) were increased in peripheral blood from patients and decreased on the treatment, whereas activated T lymphocytes increased after therapy in those with better overall survival. Conclusions: In conclusion, blood concentration of MDSCs and Treg cells may be good prognostic markers for overall survival after 2 years in R/R DLBCL. These results point to a possible role of these elements in the immunosuppression of these patients, as assessed by the circulating activated and inhibited T lymphocytes, and therefore, they may be considered as therapeutic targets in DLBCL.